2021
DOI: 10.1021/acsabm.1c00880
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Multifaceted Next-Generation Technologies for Improved Skin Wound Healing

Abstract: Dysregulation of sequential and synchronized events of skin regeneration often results in the impairment of chronic wounds. Conventional wound dressings fail to trigger the normal healing mechanism owing to the pathophysiological conditions. Tissue engineering approaches that deal with the fabrication of dressings using various biomaterials, growth factors, and stem cells have shown accelerated healing outcomes. However, most of these technologies are associated with difficulties in scalability and cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 266 publications
(413 reference statements)
0
14
0
Order By: Relevance
“…The antimicrobial property is one important characteristic of hydrogels intended for wound-healing applications. These hydrogels are capable of reducing the risk of bacterial infection on-site during their application and use, which could consequently impede the regeneration of the skin E.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antimicrobial property is one important characteristic of hydrogels intended for wound-healing applications. These hydrogels are capable of reducing the risk of bacterial infection on-site during their application and use, which could consequently impede the regeneration of the skin E.…”
Section: Resultsmentioning
confidence: 99%
“…These hydrogels are capable of reducing the risk of bacterial infection on-site during their application and use, which could consequently impede the regeneration of the skin. 6 E. coli, P. aeruginosa, and S. aureus are among the most common pathogens that colonize wounds. 44 Pathogen infection leads to dysregulation of the sequential and synchronized events of the wound-healing process.…”
Section: Chemical Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Physiological electric fields are important factors in the control and regulation of tissue homeostasis, and the use of external ES to regulate cell migration and enhance regeneration of tissues and healing of wounds has become a common practice. , However, the effect of internal wireless ES based on piezoelectric nanomaterials on the migration of carcinoma cells is unclear. To prove the role of ES treatment during metastasis, we designed a wound healing assay.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, our results demonstrated that internal ES generated by USdriven BTNPs could activate the cell cycle-apoptosis pathway similar to that of TTF, in which BTNPs were involved in regulation as direct effector elements rather than TTF-auxiliary sensitizers. 17 40,41 However, the effect of internal wireless ES based on piezoelectric nanomaterials on the migration of carcinoma cells is unclear. To prove the role of ES treatment during metastasis, we designed a wound healing assay.…”
Section: Cell Cycle Arrest and Apoptosis Induced By Es In Vitromentioning
confidence: 99%